Logic Pro X 10.1 - Nahmani, David (Peachpit Press, 2015)
Please note: Updates for Logic Pro v10.2 can be found at www.peachpit.com/apts.logicprox101 on the Updates tab. Completely revised and updated for Logic Pro v10.2, this Apple-certified guide shows you how to record, produce, and make music files that stand out with the Apple professional audio software. Veteran music producer David Nahmani's step-by-step instructions teach you everything from basic music creation to professional production techniques using Logic's software synthesizers, samplers, and digital signal processors. You'll learn about all of the key features in Logic Pro v10.2 and use the book's online files to begin making music from the very first lesson. Whether you're looking to use your computer as a digital recording studio, create musical compositions, or transfer that song in your head into music you can share, this comprehensive book will show you how.
"Apple certified.". - Includes index. - Online resource; title from title page (Safari, viewed July 20, 2015)
Keywords: Logic (Computer file); Sound -- Recording and reproducing -- Digital techniques; Computer sound processing; Son; Traitement par ordinateur; Sound; Recording and reproducing; Digital techniques